PENGARUH KESADARAN BERAGAMA TERHADAP PELECEHAN SEKSUAL DI KALANGAN SANTRI: Studi Kuantitatif di Kalangan Santri - Aliffia, Fatma Maulla; Marisannatulhaq, Marisannatulhaq (Islamic Education Department, Islamic University of Majapahit (Universitas Islam Majapahit) Mojokerto, Indonesia, 2024)
This study aims to explore the relationship between religious awareness and sexual harassment behavior among students at Pondok Pesantren Roudlotul Rohmah Sooko. Data was collected through a structured questionnaire involving 35 respondents and analyzed using Pearson's correlation test. The results show that the majority of the students have a high level of religious awareness, with an average score of 62, while sexual harassment-related behavior also shows significant figures, with an average score of 38.4. The correlation test indicates a positive relationship between religious awareness and understanding of sexual harassment behavior (r = 0.344, p = 0.043), although this relationship is considered low. These findings contradict the initial hypothesis, which expected a negative relationship between the two variables. This study suggests the need for a multidimensional approach in religious education and sexual harassment prevention, including curriculum development covering religious awareness topics and training to recognize signs of sexual harassment, as well as creating a safe and supportive environment in educational institutions and society.